Semi-Automatic Identification of the Fetal Profile and Nasal Bone Measurement at the Time of the Routine Mid-Trimester Ultrasound Scan - Weichert, A.; Neymeyer, J.; Hinkson, L.; Weichert, T. M.; Schmiedel, D.; Kalache, K. D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: This study was designed to compare nasal bone length (NBL) measurements using a manual multiplanar mode with those made using a newer semi-automatic technique (Volume NT™) acquired by an experienced operator as well as measurements done by two independent observers with different levels of ultrasound experience (conventional 2 D vs. Volume NT™).Materials and Methods: Ultrasound examination was performed prospectively on 81 pregnant women with a singleton pregnancy at the time of their routine mid-trimester ultrasound scan.Results: The correct mid-sagittal plane of the fetal profile was successfully obtained using the semi-automatic technique in 53 of 81 cases.Conclusion: NBL measurements using conventional two-dimensional techniques showed significantly higher inter-observer variability than the semi-automatic program. Our study shows the feasibility of using a semi-automatic technique, especially for less experienced operators. Measurements obtained with the semi-automatic technique produced much less variable results around a mean than those obtained with conventional two-dimensional ultrasound.
Keywords: face; nasal bone; 3 D ultrasound; image manipulation/reconstruction; observer performance